2020
DOI: 10.1002/ijfe.1807
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous investment horizons, risk regimes, and realized jumps

Abstract: This paper introduces a new empirical framework to identify the regimes of jump‐type tail risk over multiple trading horizons. Our approach combines the hidden Markov regime‐switching model with realized jumps, which allows us to examine the tail risk exposure of investors at different investment scales. Applying our method to data on bonds, stocks, and currencies, we find evidence that market risk linked to jumps exhibits time‐varying regime shifts and horizon‐dependence. We show that high‐frequency trading d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…For investors with different investment horizons, the effects of jumps with multi-time scales may be not the same due to the heterogenous investment horizon ( Dai et al, 2020 ; Wang et al, 2020b ; Dai et al, 2021b ; Miao et al, 2022 ). For investors with short investment horizons, the short-term effects of stock price jumps will bring the most intuitive and significant losses ( Erdemlioglu and Gradojevic, 2021 ). Conversely, for investors with long investment horizons, long-term effects may change the fundamentals of the industries and impact the adjustments to their investment strategies ( Yang et al, 2016 ; Jorion, 2000 ; Bakshi et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…For investors with different investment horizons, the effects of jumps with multi-time scales may be not the same due to the heterogenous investment horizon ( Dai et al, 2020 ; Wang et al, 2020b ; Dai et al, 2021b ; Miao et al, 2022 ). For investors with short investment horizons, the short-term effects of stock price jumps will bring the most intuitive and significant losses ( Erdemlioglu and Gradojevic, 2021 ). Conversely, for investors with long investment horizons, long-term effects may change the fundamentals of the industries and impact the adjustments to their investment strategies ( Yang et al, 2016 ; Jorion, 2000 ; Bakshi et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…Literature [20] designed a robust irreversible investment rule applicable to a series of neighboring models and found that investment decisions are driven by fuzzy aversion as long as they are driven by the magnitude of the value jumps, not the frequency. In literature [21], a new empirical framework is introduced to identify jump tail risk mechanisms across multiple trading horizons. Analytical tests have demonstrated that the premium for jump risk is influenced by market risk and the frequency of investments in financial assets by investors.…”
Section: Introductionmentioning
confidence: 99%
“…The failure of several financial institutions may lead to a severe economic crisis [ 8 , 9 , 10 ]. One of the typical examples is the global financial crisis triggered by the collapse of Lehman Brothers in 2008 [ 11 , 12 , 13 ]. Therefore, how to accurately evaluate the systemic importance of financial institutions (SIFIs) so as to provide early warning and deal with the crisis effectively has become an emergent work [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%